Medical students’ research productivity and career preferences; a 2-year prospective follow-up study - Möller, Riitta (BMC Med Educ, 2017)
BACKGROUND: Linking undergraduate medical education to scientific research is necessary for the quality of future health care, and students´ individual research projects are one way to do so. Assessment of the impact of such projects is of interest for both educational and research-oriented segments of medical schools. Here, we examined the scholarly products and medical students’ career preferences 2 years after a mandatory research project course. METHODS: A prospective cross-sectional questionnaire study. All 581 students registered on a 20-week research project course between September 2010 through September 2012 were e-mailed a questionnaire 2 years after completing the course. RESULTS: In total, 392 students (mean age 27 years; 60% females) responded (67% response rate). 59 students (15%) were co-authors on a scientific paper published in an international journal, 6 students had published in a national journal, and 57 students had co-authored a paper submitted for publication. Totally, 122 scientific papers had been submitted. Moreover, 67 (17%) students had given 107 oral or poster presentations nationally or internationally during the follow-up. Career-wise, 36 students (9%) had been registered as PhD students and an additional 127 students (34%) were planning to register. Those who did not plan doctoral studies were significantly older (p = 0.013) than those who did. However, 35% reported that they would in the coming 5 years prefer to work as clinicians only, and this group was significantly younger than those who envisaged participation in research. There were no significant gender differences. CONCLUSIONS: Approximately a third of the students had authored papers and/or public presentations, and a similar fraction had career plans involving a PhD degree. The results indicate that the project course had a positive impact on continued supervisor-student collaboration on a professional level, but also that strategies to encourage young doctors to perform clinical research may be needed.